Inspirasi Model Connect the Dots Bagi Startup Bisnis Industri Jobshop (Studi Kasus PT. RMB) - Pandena Kicky Basuki Putri; Yudhanegara, Darmawan (Sekolah Tinggi Teknologi Wastukancana, 2024)
The goal of business startupsto build of industry is to increaseof industrial development in Indonesia and its organizations too. RMB is built to determine achieve of national and organizational goals in the manufacturing sector inside. Start-up industries have the goal of ensuring that the industry can operate and be profitable in a sustainable manner. The inspiration for the Connect the Dots model became the model used in making business establishment decisions. Apart from the initiation process, it is included in determining future business operations, which has resulted in research that starting a manufacturing industry business can run profitably and operate sustainably if it has the confidence of the actor to encourage it from within